Biofortification of Cereals and Pulses Using New Breeding Techniques: Current and Future Perspectives - Shahzad, Rahil; Jamil, Shakra; Ahmad, Shakeel; Nisar, Amina; Khan, Sipper; Amina, Zarmaha; Kanwal, Shamsa; Aslam, Hafiz Muhammad Usman; Gill, Rafaqat Ali; Zhou, Weijun (Frontiers in Nutrition, 2021)
Cereals and pulses are consumed as staple food in low income countries for fulfillment of daily dietary requirements and as source of micronutrients. However they are failing to offer balanced nutrition due to deficiencies of some essential compounds and micronutrients i.e. cereals are deficient in iron, zinc, some essential amino acids and low quality proteins whereas pulses are rich in anti-nutrient compounds which restricts the bioavailability of micronutrients. As a result population is suffering from malnutrition and resultantly different diseases i.e. anemia, beriberi, pellagra, night blindness, rickets and scurvy are common in these societies. These established facts highlight the need of biofortification of cereals and pulses for offering of balanced diets to masses and reduction of malnutrition. Biofortification of crops may be achieved through conventional approaches i.e. fertilization and conventional breeding or through new breeding techniques i.e. transgenic breeding and genome editing. We have highlighted the significance of conventional vs new breeding techniques and different avenues and opportunities for biofortification of crops. Conventional approaches for biofortification covers mineral fertilization through foliar or soil application, microbe-mediated enhanced uptake of nutrients, and conventional crossing of plants to obtain the desired combination of genes for balanced nutrient uptake and bioavailability. Whereas new breeding techniques rely on gene silencing, gene editing, overexpression, and gene transfer from other species for the acquisition of balanced nutritional profiles in the mutant plants. We have discussed in detail the role of new breeding techniques for the biofortification of crops alongside future perspectives. Further regulatory aspects of genome editing and transgenic crops were also discussed for a better understanding of the readership.